Chinese hamster ovary (CHO-K1) cells expressed native insulin-like growth factor-1 (IGF-1) gene towards efficient mammalian cell culture host system - Packeer Mohamed, Vasila; Hashim, Yumi Zuhanis Has-Yun; Amid, Azura; Mel, Maizirwan; Kamarulzaman, Abdul Razak; Abdul Wahab, Muhammad Adil; Mohmad Saberi, Salfarina Ezrina (Academic Journals, 2011)

(untitled)
Insulin-like growth factor-1 (IGF-1) has been shown to promote cell proliferation and inhibit apoptosis of cells. These are two characteristics of mammalian cell culture which may lead to high density cell culture producing optimal desired yield of bioproducts. An inherent secretion of IGF-1 protein from host cells into the culture media is hypothesized to enable reduction or removable of serum from culture media, thus reducing cost. This study was set to investigate the IGF-1 gene expression in Chinese hamster ovary (CHO-K1) cells. The cells were first cultured in T-flask with three independent experiments. An 8-hourly sampling for responses (glucose, lactate, total protein and biomass) was done. PCR-based method was performed to study the expression of IGF-1 gene. To this end, it was confirmed that CHO-K1 cells used in this study expressed IGF-1 gene. The study also provides the baseline data on kinetics and biochemical responses of CHO-K1 cell growth. Together, the data would be particularly useful for further studies using CHO-K1 cells as efficient mammalian cell culture host system to produce biologics.